Viral Load Kinetics of Severe Acute Respiratory Syndrome Coronavirus 2 in Hospitalized Individuals With Coronavirus Disease 2019. (17th April 2021) - Regan, James; Flynn, James P; Rosenthal, Alexandra; Jordan, Hannah; Li, Yijia; Chishti, Rida; Giguel, Francoise; Corry, Heather; Coxen, Kendyll; Fajnzylber, Jesse; Gillespie, Elizabeth; Kuritzkes, Daniel R; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) kinetics remain understudied, including the impact of remdesivir. In hospitalized individuals, peak sputum viral load occurred in week 2 of symptoms, whereas viremia peaked within 1 week of symptom-onset, suggesting early systemic seeding of SARS-CoV-2. Remdesivir treatment was associated with faster viral decay.